2021
DOI: 10.2807/1560-7917.es.2021.26.22.2001536
|View full text |Cite
|
Sign up to set email alerts
|

Lockdown as a last resort option in case of COVID-19 epidemic rebound: a modelling study

Abstract: Background Given its high economic and societal cost, policymakers might be reluctant to implement a large-scale lockdown in case of coronavirus disease (COVID-19) epidemic rebound. They may consider it as a last resort option if alternative control measures fail to reduce transmission. Aim We developed a modelling framework to ascertain the use of lockdown to ensure intensive care unit (ICU) capacity does not exceed a peak t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…FTTIS measures and the rapid expansion of vaccine coverage will reduce the susceptible population and reduce the contact frequency and contact probability between infected and susceptible people. This should reduce cases and deaths in the long run [ 30 ]. A study in France found that most COVID-19 cases were undetected, especially when the incidence was high.…”
Section: Discussionmentioning
confidence: 99%
“…FTTIS measures and the rapid expansion of vaccine coverage will reduce the susceptible population and reduce the contact frequency and contact probability between infected and susceptible people. This should reduce cases and deaths in the long run [ 30 ]. A study in France found that most COVID-19 cases were undetected, especially when the incidence was high.…”
Section: Discussionmentioning
confidence: 99%
“…Variants of concern (VOC) of SARS-CoV-2 with increased transmissibility, such as the Delta (B.1.617.2) and, more recently, the Omicron (B.1.1.529) variants, have led to a substantial surge in the incidence rate of severe COVID-19 cases, particularly in the context of low vaccine coverage and especially in lower-middle and low-income countries. As a result, in many countries the saturation of intensive care units (ICU) has driven political decisions, including containment and segregation measures [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, in many countries the saturation of intensive care units (ICU) has driven political decisions, including containment and segregation measures. 23…”
Section: Introductionmentioning
confidence: 99%